CHICKEN EGGS TO QUALITY INDICATORS EFFECT OF PROBIOTIC INNOPROVET - Z. I. Ilyosov; Yunusov X. B.; Ibragimov F. B. (Web of Journals Publishing, 2024)
The article presents information on scientific and experimental results of laboratory indicators of the quality of eggs of laying hens.
Keywords: Poultry, chicken, egg, laboratory, quality indicator.